Preoperative POPQ versus Simulated Apical Support as a Guideline for Anterior or Posterior Repair at the Time of Transvaginal Apical Suspension (PREPARE trial): study protocol for a randomised controlled trial - Myung Jae Jeon; Chul Hong Kim; Hyun-Hee Cho; Dong Hoon Suh; Soo Rim Kim (BMJ Open)
Introduction Transvaginal reconstructive surgery is the mainstay of treatment for symptomatic pelvic organ prolapse. Although adequate support for the vaginal apex is considered essential for durable surgical repair, the optimal management of anterior and posterior vaginal wall prolapse in women undergoing transvaginal apical suspension remains unclear. The objective of this trial is to compare surgical outcomes of pelvic organ prolapse quantification (POPQ)-based surgery with outcomes of simulated apical support-based surgery for anterior or posterior vaginal wall prolapse at the time of transvaginal apical suspension.Methods and analysis This is a randomised, multicentre, non-inferiority trial. While women who are assigned to the POPQ-based surgery group will undergo anterior or posterior colporrhaphy for all stage 2 or greater anterior or posterior vaginal prolapse, those assigned to simulated apical support-based surgery will receive anterior or posterior colporrhaphy only for the prolapse unresolved under simulated apical support. The primary outcome measure is the composite surgical success, defined as the absence of anatomical (anterior or posterior vaginal descent beyond the hymen or descent of the vaginal apex beyond the half-way point of vagina) or symptomatic (the presence of vaginal bulge symptoms) recurrence or retreatment for prolapse by either surgery or pessary, at 2 years after surgery. Secondary outcomes include the rates of anterior or posterior colporrhaphy, the changes in anatomical outcomes, condition-specific quality of life and sexual function, perioperative outcomes and adverse events.Ethics and dissemination This study was approved by the institutional review board of each participating centre (Seoul National University College of Medicine/Seoul National University Hospital, Chonnam National University Hospital, Seoul St. Mary’s Hospital, International St. Mary’s Hospital). The results of the study will be published in peer-reviewed journals, and the findings will be presented at scientific meetings.Trial registration number NCT03187054